Intelligent Health Monitoring System - R. V. Kaulgud, Rutuja Patil; Priyanka Suryawanshi; Sunetra Chavan (Journal of Electronic Design Engineering, 2021)
In this paper we are going to observe the patient’s health without vising them i.e. we observe them remotely. We have four sensors temperature sensor, oxygen level sensor, humidity sensor by using these sensors we measure the parameters and transfer all this information through the IoT cloud to the website. We can also store that information on the website. If patients are in emergency cases then it directly informs the doctors through the emergency switch. We can also add more parameters to measure. We are going to measure the four parameters by using two sensors. This device is useful in the current situation. A large number of the people were ill due to corona and day by day the numbers are increasing, so due to this, we are facing a shortage of medical help. Hence by using this device we can manage the situation. The patient who has serious issues was admitted and the remaining was observed through this device at their home.